Routledge International Handbook of Clinical Suicide Research - Cutcliffe, John (2014)
Suicide remains one of the most pressing public health concerns across the world. Expensive in terms of the human cost and associated suffering, the economic costs, the social costs and the spiritual costs, it affects millions of people every year. This important reference work collects together a wide range of research around suicide and suicide prevention, in order to guide future research and provide guidance for professionals about the best way to respond meaningfully to suicidal patients. Responding to the need for multi-disciplinary and international research to deepen our understanding of suicide, it demonstrates where our knowledge is firmly evidence-based and where new areas for research are emerging, as well as highlighting where we know little. Divided into six parts, each with its own editorial introduction and commentary, it explores research with and about survivors of suicide and indigenous populations. The remaining sections look at suicide-focused research in psychiatric nursing, psychiatry, psychology, and social work and allied health. It is of interest to all advanced students, practitioners and scholars interested in suicide and its impact and prevention.